2020
DOI: 10.1093/imanum/draa085
|View full text |Cite
|
Sign up to set email alerts
|

A posteriori error estimates with boundary correction for a cut finite element method

Abstract: In this work we introduce, analyze and implement a residual-based a posteriori error estimation for the CutFEM fictitious domain method applied to an elliptic model problem. We consider the problem with smooth (nonpolygonal) boundary and, therefore, the analysis takes into account both the geometry approximation error on the boundary and the numerical approximation error. Theoretically, we can prove that the error estimation is both reliable and efficient. Moreover, the error estimation is robust in the sense … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The computation of this term, however, is not trivial and requires the construction of a sub mesh. Nevertheless, numerical results have shown that such error is not necessary to compute since the boundary approximation error can already be captured by the residual based error estimator in [18]. In this paper, we also discard such term and the numerical results also confirm that our error estimator is able to catch both the boundary approximation errors and the discretization error due to the numerical method.…”
mentioning
confidence: 51%
See 4 more Smart Citations
“…The computation of this term, however, is not trivial and requires the construction of a sub mesh. Nevertheless, numerical results have shown that such error is not necessary to compute since the boundary approximation error can already be captured by the residual based error estimator in [18]. In this paper, we also discard such term and the numerical results also confirm that our error estimator is able to catch both the boundary approximation errors and the discretization error due to the numerical method.…”
mentioning
confidence: 51%
“…Remark 4.4. From the above estimate, we observe that can be bounded by the residual based error estimator given in [18]. Moreover, the constants are uniformly bounded and independent of the domain-mesh intersection.…”
Section: Hementioning
confidence: 90%
See 3 more Smart Citations